A retrospective study comparing the efficiency of recurrent LSIL cytology to high-grade cytology as predictors of high-grade cervical intraepithelial neoplasia or worse (CIN2+). Issue 1 (3rd December 2021) - Suleman, R; Botha, MH
Abstract : Background: Cervical cancer (CC) is one of the most preventable cancers; however, it is the leading cause of cancer-related female deaths in South Africa. This study aimed to compare the efficiency of recurrent low-grade squamous intraepithelial lesion (LSIL) cytology as criteria to predict CIN2+ incidence, to a single initial high-grade squamous intraepithelial lesion (HSIL) cytology. Methods: A retrospective cohort study comprising 344 women was conducted from January 2014 to December 2018 at the Colposcopy Clinic, Tygerberg Hospital. The women were categorised into two groups: (1) women with a recurrent LSIL cytology result, with recurrent cytology scheduled within 6–12 months; (2) women diagnosed with a single initial HSIL cytology result. The outcome was dichotomised into (1) normal or cervical intraepithelial neoplasia 1 (<CIN2) and (2) cervical intraepithelial neoplasia 2/3 or CC (CIN2+). Pearson's chi-square test (X 2 ) and Fisher's exact test were used to assess any association between the patient-related factors considered and CIN2+ incidence. Results: The sensitivity, specificity, PPV and NPV for referral HSIL cytology was 72.73% (95% CI 65.96–78.80), 79.10% (95% CI 71.24–85.64), 83.72% (95% CI 78.54–87.85) and 66.25% (95% CI 60.61–71.46), respectively. HIV status ( p  = 0.012) and ARV treatment ( p  = 0.015) were found to have statistically significant associations with CIN2+ incidence. Conclusions: A single initial HSIL result is a more efficient predictor of CIN2+ incidence compared with a recurrent LSIL cytology result. The HIV-negative women were more accurately identified as CIN2+, compared with HIV-positive women. Women not on ARV treatment were more accurately identified as <CIN2+, compared with women on ARV treatment.